K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 12 2020

a, \(5x-20y=5\left(x-4y\right)\)

b, \(x^3-9x=x\left(x^2-9\right)=x\left(x-3\right)\left(x+3\right)\)

c, \(x^2-2xy-y^2-16=-\left(x+y\right)^2-16=-\left(x+y-4\right)\left(x+y+4\right)\)

23 tháng 11 2018

a) x4-9x2

(x2-3x)(x2+3x)

x2(x-3)(x+3)

23 tháng 11 2018

x2+y2+2xy-9

(x+y)2-32

(x+y-3)(x+y+3)

24 tháng 7 2016

a. 2xy - x2 - y2 + 16

=(2xy-x2-y2)+16 

=16-(x-y)2

=(4+x-y)(4-x+y)

b. x2 + x - 6

=x2+3x-2x-6

=x(x+3)-2(x+3)

=(x-2)(x+3)

c. x2 + 5x + 6

=x2+3x+2x+6

=x(x+3)+2(x+3)

=(x+2)(x+3)

1 tháng 11 2020

a) \(9x^2-12x+4\)

\(=9x^2-6x-6x+4\)

\(=3x\left(3x-2\right)-2\left(3x-2\right)\)

\(=\left(3x-2\right)^2\)

b) \(2xy+16-x^2-y^2\)

\(=-\left(x^2-2xy+y^2-16\right)\)

\(=-\left(x-y\right)^2+16\)

\(=\left(4-x+y\right)\left(4+x-y\right)\)

c) \(3x+2x^2-2\)

\(=2x^2+4x-x-2\)

\(=2x\left(x+2\right)-\left(x+2\right)=\left(x+2\right)\left(2x-1\right)\)

25 tháng 10 2015

\(a,y-x^2y+2xy^2-y^3=y(1-x^2+2xy-y^2) =y[1-(x^2-2xy+y^2)]=y[1-(x-y)^2] =y(1-x+y)(1+x-y) =y(x+y-1)(x-y+1) \)

20 tháng 10 2019

1) Ta có: 2xy - x2 - y2 + 16

= -(x2 - 2xy + y2 - 16)

= -[(x - y)2 - 16]

= -(x - y - 4)(x - y + 4)

2) x3 + 2x2y + xy2 - 9x

= x(x2 + 2xy + y2 - 9)

= x[(x + y)- 9]

= x(x + y  - 3)(x + y + 3)

3) x4 - 2x2 = x2(x2 - 2)

20 tháng 10 2019

1. 2xy-x2-y2+16= -(x2-2xy+y2-16) = -(x2-2xy+y2)-16 = -(x-y)2-16= (x+y)2-42= (x+y-4).(x+y+4)

2. x3+2x2y+xy2-9x= (có sai đề không vậy?)

26 tháng 11 2017

a) \(x^2-xy+x-y\)

\(=\left(x^2-xy\right)+\left(x-y\right)\)

\(=x\left(x-y\right)+\left(x-y\right)\)

\(=\left(x+1\right)\left(x-1\right)\)

b) \(2xy-x^2-y^2+16\)

\(=16-\left(x^2-2xy+y^2\right)\)

\(=4^2-\left(x-y\right)^2\)

\(=\left(4-x+y\right)\left(4+x-y\right)\)

c) \(x^2-6x-16\)

\(=x^2-6x+9-25\)

\(=\left(x^2-6x+9\right)-25\)

\(=\left(x-3\right)^2-5^2\)

\(=\left(x-3-5\right)\left(x-3+5\right)\)

\(=\left(x-8\right)\left(x+2\right)\)

26 tháng 11 2017

a)  x2 - xy + x - y = x(x - y) + (x - y) = (x - y)(x + 1)

b) 2xy - x2 - y2 + 16 = 16 - (x - y) = (4 - x + y)(4 + x - y)

c) x2 - 6x - 16 = (x - 3)2 - 25 = (x - 3 - 5)(x - 3 + 5) = (x - 8)(x + 2)

16 tháng 11 2018

b.10x(x-y)-6y(y-x)=10x(x-y)+6y(x-y)=(10x+6y)(x-y)

16 tháng 11 2018

c.3x2+5y-3xy-5x=(3x2--3xy)-(5x-5y)=3x(x-y)-5(x-y)=(3x-5)(x-y)

20 tháng 10 2019

a) \(3x^2-5x-8\)

\(=3x^2+3x-8x-8\)

\(=3x\left(x+1\right)-8\left(x+1\right)\)

\(=\left(x+1\right)\left(3x-8\right)\)

b) \(x^4+6x^3+9x^2-16\)

\(=\left(x^2+3x\right)^2-16\)

\(=\left(x^2+3x-4\right)\left(x^2+3x+4\right)\)

\(=\left(x^2-x+4x-4\right)\left(x^2+3x+4\right)\)

\(=\left[x\left(x-1\right)+4\left(x-1\right)\right]\left(x^2+3x+4\right)\)

\(=\left(x-1\right)\left(x+4\right)\left(x^2+3x+4\right)\)